Pengungkapan Inovasi Disruptif Sektor Perbankan Indonesia - Sabina Sabina; Lilik Handajani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The banking industry in Indonesia is experiencing significant disruption due to the development of information and communication technology. Disruption brings new innovations that change the way banks serve customers. One form of disruptive innovation is fintech (fintech technology) which offers financial services that are more accessible, cheap and efficient. Disclosure of disruptive innovations is important for banks to inform stakeholders about their strategies and plans to deal with disruption. This disclosure can improve the transparency and accountability of banks, as well as help investors and creditors in assessing risks and investment opportunities. This study aims to determine the effect of financial capital, human capital and organizational capital on the disclosure of disruptive innovation in the Indonesian banking sector. The population in this study are banking companies listed on the IDX in 2018-2022. This study uses purposive sampling technique. Based on these criteria and sampling techniques, 45 banking sector companies were obtained with a five-year observation period, so that the total sample obtained was 225 samples. The data analysis technique used is panel data regression with the eviews 12 application. The results of this study indicate that financial capital and human capital affect the disclosure of disruptive innovation in the Indonesian banking sector. Meanwhile, organizational capital has no effect on the disclosure of disruptive innovation. This study also found that the level of debt, bank size and ROA as control variables were unable to show the effect of disclosure on disruptive innovation in the Indonesian banking sector.